The age, NT-proBNP, and Ejection Fraction Score as a Novel Predictor of Clinical Outcomes in CAD Patients After PCI. (July 2022) - Fan, Lei; Zhang, Zeng-Lei; Tang, Jun-Nan; Guo, Qian-Qian; Zhang, Jian-Chao; Cheng, Meng-Die; Song, Feng-Hua; Liu, Zhi-Yu; Wang, Kai; Jiang, Li-Zhu; Yue, Xiao-Ting; Bai, Yan; et al.
Background: Previous evidences have been proved that age, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and ejection fraction are tightly associated with the long-term outcomes in patients suffered from coronary artery disease (CAD). Therefore, the present study aimed to assess the prognosis value of age, NT-proBNP, and ejection fraction (ABEF) score in CAD patients who underwent percutaneous coronary intervention (PCI). Methods: Observational cohort methodology was used in this study which enrolled totally 3561 patients. And the patients were followed up regularly for 37.59 ± 22.24 months. Patients were classed into three groups based on the tertiles of ABEF sore: first tertile (<5.06, n = 831), second tertile (5.06-6.25, n = 839), and third tertile (≥ 6.25, n = 834). The ABEF score was calculated as follows: age (years)/ejection fraction (%) + NT-proBNP (NT-proBNP<177pg/mL was 1, 177≤NT-proBNP≥524pg/mL was 2 and NT-proBNP > 524pg/mL is 3). The association between ABEF score and adverse prognosis, including all-cause death (ACD), cardiac death (CD), major adverse cardiovascular events (MACEs) and major adverse cardiac and cerebrovascular events (MACCEs), in patients who underwent PCI was analyzed. Results: According to the risk category of ABEF score, the incidences of ACD ( P  < .001), CD ( P  < .001) and MACCEs ( P  = .021) among the three groups showed significant differences. Multivariate Cox regression analysis suggested that the respective risks of ACD and CD were increased 3.013 folds (hazard risk [HR] = 4.013 [95% confidence interval [CI]: 1.922-8.378], P  < .001) and 4.922 folds ([HR] = 5.922 [95% [CI]: 2.253-15.566], P  < .001) in the third tertile compared with those in the first tertile. Kaplan-Meier survival analyses showed that the cumulative risks of ACD, CD and MACCEs in patients with the high ABEF score tended to increase. Conclusion: The present study indicated ABEF score was a novel biomarker suitable for predicting adverse prognosis in patients after PCI, which may be used for early recognition and risk stratification.